Stability of Dengue 2 Nonstructural Glycoprotein 1 (NS1) Is Affected by the Nature of Basic Residue at Position NS1-324 - Ogire, Eva; El-Kalamouni, Chaker; Desprès, Philippe; Roche, Marjolaine (Current Issues in Molecular Biology, 2023)
Dengue is the most prevalent mosquito-borne viral disease. It is caused by the infection of any of the four dengue virus (DENV) serotypes DENV-1 to DENV-4. The DENV non-structural glycoprotein 1 (NS1) plays an important role in virus replication and the immunopathogenesis of virus infection. The NS1 protein has been identified as both a cell-associated homodimer and a soluble secreted lipoprotein nanoparticle. The nature of the residues at positions NS1-272 and NS1-324 in the β-ladder domain may have an effect on the biological behaviors of DENV-2 NS1 protein in human hepatoma Huh7 cells. The stability of the NS1 protein from the Reunion 2018 DENV-2 strain was affected by the presence of lysine residues at positions 272 and 324. In the present study, we evaluated the impact of mutations into lysine at positions 272 and 324 on recombinant NS1 protein from the DES-14 DENV-2 strain bearing arginine residue on these two positions. The DES-14 NS1 protein mutant bearing a lysine at position 324 was deficient in protein stability and secretion compared to wild-type protein. The defect in the DES-14 NS1 protein mutant was associated to oxidative stress and pro-inflammatory cytokine activation in Huh7 cells. The ubiquitin-proteasome proteolytic pathway might play a key role in the stability of DENV-2 protein bearing a lysine residue at position 324.